Multimedia in Social Work Education: An In-Depth Exploration of Current Practices and Challenges in Bangladeshi Government Colleges - Ahasan, Md. Habibul (Universitas Majalengka, 2024)
The purpose of this study was to investigate the current practices, opportunities, and challenges of using multimedia in social work teaching at a government college in Bhola, Bangladesh. Qualitative research methodology was used to get information from the respondents. The data was gathered using three different methods: semi-structured interviews, focus group discussions (FGDs), and classroom observations. The respondents included both faculty and honors-level students from social work backgrounds. Interviews were conducted with two instructors, observations were made in two classes, and ten students took part in two focus group discussions (FGDs). Finally, using a thematic approach, data were analyzed, interpreted, and presented. The study's findings revealed that incorporating multimedia in the classroom makes teaching easier and is beneficial for the students. Students can actively engage in a multimedia classroom, which often inspires them to study. People perceive multimedia-based classes to be more structured than traditional teaching methods. Conversely, the research shows that the social work classes are deficient in the essential resources, infrastructure, and funding required for effective functioning. The study was self-funded, completed within a short timeframe, and conducted during the global outbreak of the Corona pandemic. The study's implication was that it helped the researcher explore the current scenario of using multimedia for teaching social work in the context of government college education in Bangladesh.